A SIMPLE ALGORITHM FOR FINDING FAST, EXACTLY TILES INTERSECT WITH POLYGONS - Nguyen, Nam V.; Nguyen, Nam M.; Le, Bac H. (Vietnam Journal of Science and Technology, 2012)
In this article, we present a simple algorithm that allows us to find tiles intersect quickly and precisely with a given polygon. This is the one of important tasks in maintaining tile system for Web Map services today. In this study, 75% of tiles can be successfully saved by use of our newly developed method as compared with the conventional Minimum Bounding Rectangle method when applying for administrative regions of Vietnam. In addition, this algorithm is simple and easy to implement.